2022
DOI: 10.3389/fpls.2022.855003
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Climate Sensitivity of Pinus cembra Tree-Ring Traits in the Carpathians

Abstract: High-elevation ecosystems are one of the most sensitive to climate change. The analysis of growth and xylem structure of trees from marginal populations, especially the ones growing at the treeline, could provide early-warning signs to better understand species-specific responses to future climate conditions. In this study, we combined classical dendrochronology with wood density and anatomical measurements to investigate the climate sensitivity of Pinus cembra L., a typical European high-elevation tree specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 93 publications
1
3
0
Order By: Relevance
“…Pine responded to previous spring and summer precipitation without allocating carbon resources to reinforce the hydraulic system, showing a decrease in CWT and in AD. This is in line with previous studies (Björklund et al, 2017;Știrbu et al, 2022), and it indicates the presence of a time lag in the influence that previous-year climatic conditions have on LW traits, despite their high responsiveness to current climatic conditions (Eilmann et al, 2006;Seo et al, 2008;Martin-Benito et al, 2013;Cuny and Rathgeber, 2016). These results also showed that P. sylvestris LW traits respond in similar ways to spring and to summer precipitation, thereby presenting precise regulatory mechanisms, which likely integrate local genetic adaptation and phenotypic plasticity into a coordinated response to climate; despite the different provenances of the trees, the local climate, and the different stand density at the Spanish site.…”
Section: Similar Wood Anatomical Trait Responses To Climate and Droug...supporting
confidence: 94%
“…Pine responded to previous spring and summer precipitation without allocating carbon resources to reinforce the hydraulic system, showing a decrease in CWT and in AD. This is in line with previous studies (Björklund et al, 2017;Știrbu et al, 2022), and it indicates the presence of a time lag in the influence that previous-year climatic conditions have on LW traits, despite their high responsiveness to current climatic conditions (Eilmann et al, 2006;Seo et al, 2008;Martin-Benito et al, 2013;Cuny and Rathgeber, 2016). These results also showed that P. sylvestris LW traits respond in similar ways to spring and to summer precipitation, thereby presenting precise regulatory mechanisms, which likely integrate local genetic adaptation and phenotypic plasticity into a coordinated response to climate; despite the different provenances of the trees, the local climate, and the different stand density at the Spanish site.…”
Section: Similar Wood Anatomical Trait Responses To Climate and Droug...supporting
confidence: 94%
“…The radial cell-wall thickness was positively correlated with the temperature of a later period (from mid-July to the beginning of September) [23,48]. The lumen area was negatively correlated with the temperature from the end of June to the end of August [48]. The TRW analysed in this study was a parameter, which comprised all anatomical features; thus, the relationship between TRW and daily temperature data is not so strong.…”
Section: Discussionmentioning
confidence: 66%
“…A similar pattern was found in the Alps and Carpathians, where the temperature from mid-June to the beginning of July was the most important factor for radial growth and explained by favourable conditions for the cell number and tangential cell-wall thickness. The radial cell-wall thickness was positively correlated with the temperature of a later period (from mid-July to the beginning of September) [23,48]. The lumen area was negatively correlated with the temperature from the end of June to the end of August [48].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation